Analyzing Schizophrenia by DNA Microarrays - Horváth, Szatmár; Janka, Zoltán; Mirnics, Károly (Biological psychiatry (1969), 2011)
To understand the pathological processes of schizophrenia, we must embrace the analysis of the diseased human brain: we will never be able to recapitulate the pathology of uniquely human disorders in an animal model. Based on the outcome of the transcriptome profiling experiments performed to date, it appears that schizophrenia is associated with a global gene expression disturbance across many cortical regions. In addition, transcriptome changes are present in multiple cell types, including specific subclasses of principal neurons, interneurons, and oligodendrocytes. Furthermore, transcripts related to synaptic transmission, energy metabolism, and inhibitory neurotransmission are routinely found underexpressed in the postmortem brain tissue of subjects with schizophrenia. To put these transcriptome data in biological context, we must make our data publicly available and report our findings in a proper, expanded Minimum Information About a Microarray Experiment format. Cell-type specific expression profiling and sequencing-based transcript assessments should be expanded, with particular attention to understanding splice-variant changes in various mental disorders. Deciphering the pathophysiology of mental disorders depends on integrating data from across many research fields and techniques. Leads from postmortem transcriptome profiling will be essential to generate model animals, perform tissue culture experiments, and develop or evaluate novel drugs to treat this devastating disorder.